2007
DOI: 10.1111/j.1348-0421.2007.tb03960.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Immunological Features of Oral Candidiasis

Abstract: Candida albicans (C. albicans) is the major infectious agent of oral candidiasis, and both innate immunity and cell‐mediated immune response participate in the control of the fungal infections. The aim of this study was to correlate the clinical forms of oral candidiasis with the number of colony forming units (CFU) of C. albicans in saliva and to characterize T cell response in patients with oral candidiasis. Participants included 75 subjects: 36 with lesions of candidiasis and 39 without lesions of oral cand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 26 publications
2
24
2
1
Order By: Relevance
“…In periodontitis, bacteria lead to the activation of the local immune response, leading to systemic inflammation. Similarly, immune stimulation of T cells and monocytes has been reported in response to fungal C. albicans antigens [39, 40]. However, in our study we did not find significantly increased levels of total CRP, which could suggest that local Candida -evoked oral mucosal inflammation is not causing significant activation of systemic inflammatory response.…”
Section: Discussionsupporting
confidence: 50%
“…In periodontitis, bacteria lead to the activation of the local immune response, leading to systemic inflammation. Similarly, immune stimulation of T cells and monocytes has been reported in response to fungal C. albicans antigens [39, 40]. However, in our study we did not find significantly increased levels of total CRP, which could suggest that local Candida -evoked oral mucosal inflammation is not causing significant activation of systemic inflammatory response.…”
Section: Discussionsupporting
confidence: 50%
“…Prior to treatment, a significant difference was noted for salivary flow between the control and candida groups, demonstrating the strong relationship between decreased stimulated salivary flow and candida count. Oliveira et al reported that symptoms of candidiasis were observed in all patients with <100 CFU/ml of candida per 1 mL of saliva [31], and it appears that when stimulated salivary flow, which is greater than resting flow, decreases, the suppressive effects of saliva on candida are also decreased.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that from 30 to 50 % of the population has the microorganism in the mouth and no clinical evidence of infection. The incidence increases with age, reaching close to 60 % of dentate patients over 60 years old (De Oliveira et al 2007 ).…”
Section: Oral Candidosis (Oc)mentioning
confidence: 98%
“…In these cases, the adherence of Candida to the oral epithelium is the fi rst step in the infection process and enables the yeast to overcome the normal fl ushing mechanism of body secretions (De Oliveira et al 2007 ;Sherman et al 2002 ). Candida may act as a secondary pathogen and this super infection can possibly increase the signs and symptoms of OLP, which may be referred as "burning" sensation or discomfort (Kalmar 2007 ).…”
Section: Oral Lichen Planus (Olp)mentioning
confidence: 98%